TINJAUAN PENGORGANISASIAN FUNGSI PADA DOMPET PRIA - Dena Anggita (Narada : Jurnal Desain dan Seni, 2019)
This study aims to determine the types of men's wallets along with items and what features are contained in the wallet. A wallet is a container that is used to store money or valuable cards. Along with the times and lifestyles, wallets come with various designs and features, but many wallets have changed because of the needs and development of payment technology, so users must be able to adjust wallet designs according to their needs. This study uses a qualitative method, the research method used to examine natural object conditions where the researcher is a key instrument, source and data sampling is done in a "purposive" and "snowball" technique, data collection techniques with triangulation (combined), Next, what the researchers do is interpret the results of the data analysis which will finally get a conclusion that contains the essence of all research data. The results showed that there are 5 types of men's wallets and each type of wallet has its own organizing functions and has a quick access feature.